2014
DOI: 10.1002/uog.13411
|View full text |Cite
|
Sign up to set email alerts
|

Successful induction of labor: prediction by preinduction cervical length, angle of progression and cervical elastography

Abstract: Objective To examine the potential value of preinduction cervical length, cervical elastography and angle of progression (AOP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 25 publications
(41 reference statements)
5
53
0
1
Order By: Relevance
“…After reviewing the full-text of the selected six articles, we excluded two further articles because it was not possible to extract the numbers of TP, FP, FN, and TN for an established score threshold [18,23]. Finally, four studies were included for meta-analysis [19][20][21][22].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reviewing the full-text of the selected six articles, we excluded two further articles because it was not possible to extract the numbers of TP, FP, FN, and TN for an established score threshold [18,23]. Finally, four studies were included for meta-analysis [19][20][21][22].…”
Section: Search Resultsmentioning
confidence: 99%
“…The study of Swiatkowska-Freund and Price, including 29 patients, found a significant correlation between elastographic features of the internal os and labor induction success. On the contrary, both the studies of Pereira et al and Sonnier et al, including respectively a total of 99 and 36 women, found no significant contribution from elastography for prediction of vaginal delivery and induction-to-delivery interval compared to nulliparity and cervical length [23] and for prediction of vaginal delivery within 24 h [24]. Nonetheless, the study by Sonnier et al could not be evaluated in details as only the abstract was written in English language, and was therefore excluded from the meta-analysis [24].…”
Section: The Included Studiesmentioning
confidence: 86%
See 3 more Smart Citations